2009
DOI: 10.3386/w14989
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Child Obesity Epidemic With Natural Experiments

Abstract: We utilize clinical records of successive visits by children to pediatric clinics in Indianapolis to estimate the effects on their body mass of environmental changes near their homes. We compare results for fixed-residence children with those for cross-sectional data. Our environmental factors are fast food restaurants, supermarkets, parks, trails, and violent crimes, and 13 types of recreational amenities derived from the interpretation of annual aerial photographs. We looked for responses to these factors ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 44 publications
0
27
1
Order By: Relevance
“…A recent review investigating neighborhood food environments and obesity found that most studies used cross‐sectional designs and that the relationships between food environments and weight status were mostly null . Furthermore, very few studies contended with endogeneity, and those that did focused on restaurants, mostly fast‐food restaurants . Our study adds to existing literature by examining multiple food outlet types around each child’s home.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A recent review investigating neighborhood food environments and obesity found that most studies used cross‐sectional designs and that the relationships between food environments and weight status were mostly null . Furthermore, very few studies contended with endogeneity, and those that did focused on restaurants, mostly fast‐food restaurants . Our study adds to existing literature by examining multiple food outlet types around each child’s home.…”
Section: Discussionmentioning
confidence: 94%
“…The few studies that did find statistically significant results support the current understanding of the relationship between the food environment and obesity, in that obesity is positively correlated with proximity to fast‐food restaurants and inversely correlated with supermarkets. These studies have examined particular aspects of the food environment, that is, authors have looked at the effect of supermarkets or fast‐food restaurants on weight outcome . Another key limitation of these studies is that only a few have examined the food environment around children’s homes , including very small distances (of less than 0.1 mile) in urban areas .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful empirical research has shown, however, that cues in the environment may have a great impact on these decisions. The construction of recreational amenities (fitness areas) in Indianapolis led to a significant decrease in the BMI of children visiting pediatric clinics (Sandy et al, 2009). Posting the calorie content of foods and beverages in New York City Starbucks led to a lower consumption of food calories-even extending to the behavior of commuters who later visited other Starbucks establishments in cities where there was no calorie posting (Bollinger et al, 2011).…”
Section: The Choice Approachmentioning
confidence: 99%